Population Dynamics of Hard clam (Meretrix casta, Chemnitz, 1782) in the coastal area of Laem Phak Bia: The King’s Royally Initiated Laem Phak Bia Environmental Research and Development Project, Phetchaburi Province - ขาวหิต เสถียรพงษ์; จันทร์แก้ว เกษม; อิงคพัฒนากุล วศิน; ผิวนิล อรอนงค์; บุตรสันติ์ อนุกรณ์ (KKU Science Journal, 2015)
Population dynamics of hard clam (Meretrix casta, Chemnitz, 1782) were estimated using length–frequency data from the coastal area of Laem Phak Bia: The King’s Royally Initiated Laem Phak Bia Environmental Research and Development Project, Phetchaburi Province, Thailand between May 2012 and April 2013. Monthly length frequency data of Meretrix casta were analyzed by FiSAT_II Asymptotic length (L∝) and growth co-efficient (K) were 6.56 cm and 0.88 year-1, respectively. The growth performance index ( ) was calculated with 1.56. Total mortality (Z) by length-converted catch curve was estimated at 3.10 year-1, fishing mortality (F) at 0.37 year-1, and natural mortality (M) at 2.63 year-1. The exploitation level (E) of Meretrix casta was 0.12 and the maximum allowable limit of exploitation (Emax) was 0.42. The recruitment pattern was continuous with one major peak in the months of July-October. Habitat temperatures were 28.12 to 33.48 oC (30.96±1.79oC); salinity range was from 25.50 to 31.91 psu (28.89 ± 2.17 psu); pH range was from 7.12 to 8.48 (8.06±0.39); dissolved oxygen range was from 12.36 to 26.0 mg/l (5.22±0.86 mg/l).